Exploring Translation Challenges in English-to-Indonesian Physics Terminology - Ramadani, Fitri Novi; Sabina, Sysy Nur; Wahyunengsih, Wahyunengsih (Program Studi Pendidikan Fisika STKIP Kie Raha Ternate, 2025)
This study aims to identify and analyse the difficulties encountered by physics education students in translating physics terminology from English to Indonesian. Using a mixed-methods approach, data were collected through questionnaires and interviews involving 147 students from various universities in Indonesia. The obtained results show that the difficulty of scientific translation is expressed mainly in terminology with the least difficulty in the general understandability of sentences written in a scientific text – with the results below terminology (mean 4.17), grammatical structure (mean 4.15), understanding scientific concepts (mean 4.15), and the lack of experience and exposure to English-language physics sources (mean 4.15), with the overall level of difficulty categorized as very high (mean 4.22). One of the most significant indicators influencing scientific translation’s difficulty level is insufficient mastery of conceptual issues and poor study of the practice of transience. From the above, it can be recommended that when preparing a future translation, it is necessary to provide training in situational translation in the scientific field and provide him with greater access to foreign-language scientific literature in the field to streamline scientific translation’s end in the student’s physics education. Future studies can test the effectiveness of context-based scientific translation training and examine other factors (e.g., English proficiency and translation strategies) in a broader population.